Political Advertising Saturation in the 2016 Iowa Caucuses. Issue 1 (2nd January 2022) - Newell, Jay
Abstract : Allocating the optimum amount of campaign resources to advertising is a critical question for political managers. This research presents the case of the 2016 Iowa Caucuses, in which over $46 million of broadcast television advertising was purchased on behalf of 21 Republican and Democratic candidates and run in eight media markets over 9 months. Using Federal Communication Commission (FCC)-derived data from more than 3, 700 political advertising contracts, and responses to two waves of surveys among Iowa voters, this research considers the connection between advertising weight (adspend) and political outcomes in a media-saturated campaign. In contrast to some earlier studies, increasing levels of advertising spending did not serve to activate the interest of potential voters: while it was high to begin with, and went higher during the election period, the extra advertising was not associated with additional interest. However, increased advertising did result shifting of allegiances in the crowded Republican Caucus: in markets with heavy advertising, there was more churn in candidate preference. Additionally, overall adspend was correlated modestly with political outcomes: for the most part, high-spending candidates were the most successful in gaining support at the Caucuses.